Baseline retinal nerve fiber layer thickness as a predictor of multiple sclerosis progression: New insights from the FREEDOMS II study. (15th November 2022) - Wang, Liang; Tan, Hongmei; Yu, Jian; ZhangBao, Jingzi; Huang, Wenjuan; Chang, Xuechun; Zhou, Lei; Lu, Chuanzhen; Xiao, Yiqin; Lu, Jiahong; Zhao, Chongbo; Wang, Min; et al.
Abstract: Background and purpose: The aim was to evaluate the potential of retinal nerve fiber layer thickness (RNFLT) measured with optical coherence tomography in predicting disease progression in relapsing–remitting multiple sclerosis (RRMS). Methods: Analyses were conducted post hoc of this 24‐month, phase III, double‐blind study, in which RRMS patients were randomized (1:1:1) to once daily oral fingolimod 0.5 mg, 1.25 mg or placebo. The key outcomes were the association between baseline RNFLT and baseline clinical characteristics and clinical/imaging outcomes up to 24 months. Change of RNFLT with fingolimod versus placebo within 24 months and time to retinal nerve fiber layer (RNFL) thinning were evaluated. Results: Altogether 885 patients were included. At baseline, lower RNFLT was correlated with higher Expanded Disability Status Scale score ( r  = −1.085, p  = 0.018), lower brain volume ( r  = 0.025, p  = 0.006) and deep gray matter volume ( r  = 0.731, p  < 0.0001), worse visual acuity ( r  = −19.846, p  < 0.0001) and longer duration since diagnosis ( r  = −0.258, p  = 0.018). At month 12, low baseline RNFLT (<86 μm) versus high baseline RNFLT (≥99 μm) was associated with a greater brain volume loss (percentage change −0.605% vs. −0.315%, p  = 0.035) in patients without optic neuritis history. At month 24, low baseline RNFLT versus high baseline RNFLT was associated with a higher number of new or newly enlarged T2 lesions (mean number 4.0 vs. 2.8, p  = 0.014) and a higher risk of subsequent RNFL thinning (hazard ratio 2.55; 95% confidence interval 1.84–3.53; p  < 0.001). The atrophy of the RNFL in the inferior quadrant was alleviated with fingolimod 0.5 mg versus placebo at month 24 (Δ(least squares mean) = 1.8, p  = 0.047). Conclusion: Retinal nerve fiber layer thickness could predict disease progression in RRMS. Trial registration: Clinicaltrials.gov identifier: NCT00355134, https://clinicaltrials.gov/ct2/show/NCT00355134 .